Lithium-carbon composite material, preparation method thereof and negative electrode containing lithium-carbon composite material
By using carbon nanotubes and silver wires in lithium carbon composite materials to build a porous skeleton and filling it with lithium alloys and metal lithium, the problem of structural instability of lithium carbon composite materials during battery circulation is solved, and a higher energy density is achieved and longer cycle life.
Patent Information
- Application Number
- CN202311086785.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing lithium-carbon composite materials have unstable structure during the battery cycle, resulting in attenuation of battery performance and difficulty in uniform and dense deposition of metal lithium.
Carbon sintered porous skeleton containing carbon nanotubes and silver wires are used, and lithium alloy and metal lithium are filled in the gaps of the skeleton. Through the synergy between silver wire nucleating agent and carbon nanotube skeleton, uniform deposition and structural stability of metal lithium are achieved. .
It improves the structural strength and electrochemical properties of lithium carbon composite materials, extends the cycle life of the battery, and reduces the interface internal resistance in an all-solid-state battery system.
Smart Images

Figure CN119517949A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a lithium-carbon composite material, a preparation method thereof, and a negative electrode comprising the lithium-carbon composite material. Background Art
[0002] Metallic lithium has great application value in high energy density batteries due to its high specific capacity (3860mAh / g) and low electrode potential (-3.04V Vs hydrogen standard electrode potential). However, the problems of dendrites, "dead lithium" and volume expansion of metallic lithium limit the practical application of metallic lithium anode in batteries.
[0003] A metallic lithium negative electrode with a three-dimensional skeleton structure is an effective way to solve the above problems. In order to improve the energy density of the battery, a lightweight carbon material is preferably used as the three-dimensional skeleton. However, the wettability between the carbon material and the molten lithium is poor and there are no nucleation sites on the surface of the carbon material, which is not conducive to the uniform and dense deposition of metallic lithium. Samsung Research Institute reported the preparation of a lithium-carbon negative electrode by mixing silver and conductive carbon black. Although the prepared lithium-carbon negative electrode has good performance, as the cycle proceeds, the position of the nucleating agent silver will move near the current collector and agglomerate, eventually leading to battery performance degradation.
[0004] In summary, it is of great significance to develop a lithium-carbon composite material containing a nucleating agent and having a stable structure during battery cycling. Summary of the invention
[0005] Starting from the technical problems explained above, the object of the present invention is to provide a lithium-carbon composite material, a method for preparing a lithium-carbon composite material and a negative electrode comprising the lithium-carbon composite material. The structural strength (tensile strength) of the lithium-carbon composite material according to the present invention is large, and it is suitable for industrial production. In addition, the energy density of the negative electrode using the lithium-carbon composite material according to the present invention is large, and the structure is stable during the battery cycle, so that the battery cycle life is long.
[0006] The inventors have completed the present invention after intensive and careful research.
[0007] According to one aspect of the present invention, a lithium-carbon composite material is provided, wherein the lithium-carbon composite material comprises a carbon sintered porous skeleton containing carbon nanotubes and silver wires, wherein the voids of the carbon sintered porous skeleton are filled with lithium alloy and metallic lithium.
[0008] According to certain preferred embodiments of the present invention, the silver wires are entangled by the carbon nanotubes and interspersed in the carbon sintered porous framework.
[0009] According to certain preferred embodiments of the present invention, the pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g.
[0010] According to certain preferred embodiments of the present invention, the porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%.
[0011] According to certain preferred embodiments of the present invention, the lithium-carbon composite material has a sheet structure, and a thickness of the lithium-carbon composite material is in a range of 1 μm to 5 μm.
[0012] According to certain preferred embodiments of the present invention, the carbon nanotubes are multi-walled carbon nanotubes.
[0013] According to certain preferred embodiments of the present invention, the carbon nanotubes have a diameter ranging from 1 nm to 100 nm, preferably from 5 nm to 65 nm, more preferably from 7 nm to 48 nm, and a length ranging from 3 μm to 15 μm.
[0014] According to certain preferred embodiments of the present invention, the diameter of the silver wire is in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and the length is in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm.
[0015] According to certain preferred embodiments of the present invention, the ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000.
[0016] According to certain preferred embodiments of the present invention, based on the weight of the lithium-carbon composite material being 100%, the weight of the carbon nanotubes is 2-75% by weight, preferably 7-55% by weight, and more preferably 11-46% by weight.
[0017] According to certain preferred embodiments of the present invention, based on the weight of the lithium-carbon composite material being 100%, the weight of the silver wire accounts for 0.5-25 weight %, preferably 1.2-18 weight %, and more preferably 3.5-14.5 weight %.
[0018] According to certain preferred embodiments of the present invention, based on the weight of the lithium-carbon composite material being 100%, the weight of the lithium alloy accounts for 2-57 weight %, preferably 3.6-48 weight %, and more preferably 5.4-34.5 weight %.
[0019] According to certain preferred embodiments of the present invention, based on the weight of the lithium-carbon composite material being 100%, the weight of the metallic lithium accounts for 2-95.5 weight%, preferably 10-87 weight%, and more preferably 21-75 weight%.
[0020] According to certain preferred embodiments of the present invention, the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
[0021] According to another aspect of the present invention, there is provided a method for preparing a lithium-carbon composite material, the method comprising the following steps:
[0022] (a) dispersing carbon nanotubes, silver wires, a binder and a cross-linking agent in a solvent to prepare a dispersion;
[0023] (b) treating the dispersion at high temperature to prepare a carbon sintered porous framework containing the carbon nanotubes and the silver wires;
[0024] (c) adding a lithium alloy to molten metallic lithium to prepare a lithium melt containing the lithium alloy;
[0025] (d) immersing the carbon sintered porous skeleton containing the carbon nanotubes and the silver wires into the lithium melt containing the lithium alloy, so that the lithium melt containing the lithium alloy enters the voids of the carbon sintered porous skeleton; and
[0026] (e) taking out the impregnated carbon sintered porous skeleton from the lithium melt, casting an ingot and cooling it to obtain the lithium-carbon composite material.
[0027] According to certain preferred embodiments of the present invention, the carbon nanotubes are multi-walled carbon nanotubes.
[0028] According to certain preferred embodiments of the present invention, the carbon nanotubes have a diameter ranging from 1 nm to 100 nm, preferably from 5 nm to 65 nm, more preferably from 7 nm to 48 nm, and a length ranging from 3 μm to 15 μm.
[0029] According to certain preferred embodiments of the present invention, the diameter of the silver wire is in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and the length is in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm.
[0030] According to certain preferred embodiments of the present invention, the ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000.
[0031] According to certain preferred embodiments of the present invention, the binder is selected from one or more of polyvinyl alcohol, polyvinylidene fluoride, polybutylene styrene, polystyrene, polycarboxycellulose, cyanoacrylate, polyacrylic acid, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organic fluorine polymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethyl hydroxybenzoate and its derivatives, monosaccharide or polysaccharide polymers.
[0032] According to certain preferred embodiments of the present invention, the crosslinking agent is selected from one or more of carbomer, benzoyl peroxide, diethylenetriamine, hydrated sodium borate, cellulose derivatives and isothiazolinone.
[0033] According to certain preferred embodiments of the present invention, the solvent is selected from one or more of water, tetrachloroethylene, toluene, turpentine, acetone, methyl acetate, ethyl acetate, pentane, n-hexane, cyclohexane, octane, lemon essence, alcohol, xylene, toluene cyclohexanone, isopropanol, ethyl ether, propylene oxide, methyl butyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, acetonitrile, pyridine, phenol and ethylenediamine.
[0034] According to certain preferred embodiments of the present invention, the high temperature treatment comprises heating the dispersion at a temperature of 350° C. to 800° C. for 1 to 5 hours.
[0035] According to certain preferred embodiments of the present invention, the temperature of the molten metallic lithium is in the range of 200°C to 2500°C.
[0036] According to certain preferred embodiments of the present invention, the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
[0037] According to certain preferred embodiments of the present invention, in step (a), the weight ratio of the binder, the cross-linking agent and the carbon nanotubes is (5-65):(2-25):(10-93).
[0038] According to certain preferred embodiments of the present invention, in the carbon sintered porous framework, the silver wires are entangled by the carbon nanotubes and are interspersed in the carbon sintered porous framework.
[0039] According to certain preferred embodiments of the present invention, the pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g.
[0040] According to certain preferred embodiments of the present invention, the porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%.
[0041] According to certain preferred embodiments of the present invention, the lithium-carbon composite material has a sheet structure, and a thickness of the lithium-carbon composite material is in a range of 1 μm to 5 μm.
[0042] According to another aspect of the present invention, a negative electrode is provided, wherein the negative electrode comprises the lithium-carbon composite material described above, or comprises the lithium-carbon composite material prepared according to the preparation method described above.
[0043] Compared with the prior art in this field, the lithium-carbon composite material of the present invention has at least the following advantages:
[0044] 1. The lithium-carbon composite material contains carbon nanotubes, silver wires, and lithium alloys, and the skeleton structure constructed by the three of them is more stable;
[0045] 2. The lithium-carbon composite material has a three-dimensional carbon nanotube skeleton, which can inhibit the growth of lithium dendrites and the volume expansion of the material;
[0046] 3. Carbon nanotubes are good conductors of electrons and ions. Whether in a liquid battery system or a solid-state battery system, metallic lithium can be preferentially deposited on the silver wire nucleating agent, thereby achieving uniform and dense deposition of metallic lithium on the entire multi-walled carbon nanotube skeleton;
[0047] 4. The three frameworks have obvious synergistic effects. The silver wire is interspersed in the multi-walled carbon nanotube framework and the surface is wrapped by carbon nanotubes. In addition, the carbon nanotube framework is also filled with lithium alloy. The carbon nanotubes and lithium alloy can lock the silver wire nucleating agent in a fixed position, making the electrochemical performance of the lithium-carbon composite material more stable.
[0048] 5. When the lithium-carbon composite material is used in an all-solid-state battery system, the lithium-carbon material with a three-skeleton structure is dimensionally stable. Due to the presence of the three-skeleton structure, the interface contact between the lithium-carbon composite electrode and the solid electrolyte can be maintained under relatively small external pressure, which can effectively reduce the interface internal resistance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 A scanning tunneling microscope (SEM) photograph of a carbon sintered porous framework containing carbon nanotubes and silver wires prepared in Example 1 of the present invention is shown;
[0050] Figure 2 A scanning tunneling microscope (SEM) photograph of the lithium-carbon composite material prepared in Example 1 of the present invention is shown; and
[0051] Figure 3The cycle curves of the batteries prepared in Examples 1-4 of the present invention and Comparative Examples 1-3 are shown. DETAILED DESCRIPTION
[0052] The present invention will be described in further detail below in conjunction with specific embodiments. It will be appreciated that other embodiments are contemplated and may be implemented without departing from the scope or spirit of the present invention. Therefore, the following detailed description is non-restrictive.
[0053] Unless otherwise indicated, all numbers used in the specification and claims to represent feature sizes, quantities and physicochemical properties should be understood as being modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0054] The present invention provides a lithium-carbon composite material, which has a three-dimensional carbon nanotube skeleton structure, can reduce local current density and reduce the generation of lithium dendrites; the lithium-carbon composite material contains a silver wire nucleating agent, which can induce uniform and dense deposition of metallic lithium. The carbon nanotube skeleton, the silver wire nucleating agent and the lithium alloy synergistically form a three-dimensional skeleton structure with a stable structure, which is conducive to the preparation of a lithium-carbon composite negative electrode with stable performance.
[0055] The nucleating agent in the lithium-carbon composite material will continue to expand and contract during the charge and discharge process, but due to the surface wrapped carbon nanotubes, the carbon nanotubes can adapt to the volume change of the silver wire nucleating agent, so that the silver wire is firmly fixed on the three-dimensional multi-walled carbon nanotube skeleton. At the same time, the silver wire nucleating agent runs through the carbon nanotube network, so the carbon nanotubes also have a certain restrictive effect on the nucleating agent. In addition, the compound-type lithium alloy filled in the carbon nanotube skeleton, even if the metallic lithium is pulled out, the remaining compound-type lithium alloy will not only play a structural support role for the carbon nanotube skeleton, but also restrict the silver wire nucleating agent. The carbon nanotube skeleton, the silver wire skeleton and the compound-type lithium alloy skeleton work together to ensure the structural stability of the lithium-carbon composite material. In addition, carbon nanotubes can be used as a transport medium for ions and electrons. The metallic lithium is preferentially deposited on the nucleating agent through the carbon nanotubes, and then the uniform deposition of metallic lithium is achieved on the carbon nanotube skeleton.
[0056] Specifically, the present invention provides a lithium-carbon composite material, which comprises a carbon sintered porous skeleton containing carbon nanotubes and silver wires, wherein the voids of the carbon sintered porous skeleton are filled with lithium alloy and metallic lithium. EDX energy spectrum analysis of the specific structure of the lithium-carbon composite material proves that the lithium alloy and metallic lithium exist simultaneously in the voids of the carbon sintered porous skeleton.
[0057] Preferably, by controlling the preparation process of the lithium-carbon composite material, in the carbon sintered porous skeleton, the silver wire is entangled by the carbon nanotubes and is interspersed in the carbon sintered porous skeleton.
[0058] Preferably, the pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g. In addition, preferably, the porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%.
[0059] According to the technical solution of the present invention, the lithium-carbon composite material can be used as a negative electrode of a lithium-ion battery. Preferably, the lithium-carbon composite material has a sheet structure, and the thickness of the lithium-carbon composite material is in the range of 1 μm to 5 μm.
[0060] Preferably, in order to better achieve the mechanical and electrical effects of the lithium-carbon composite material described in detail above, the carbon nanotubes are multi-walled carbon nanotubes.
[0061] Preferably, the diameter of the carbon nanotube is in the range of 1 nm to 100 nm, preferably 5 nm to 65 nm, more preferably 7 nm to 48 nm, and the length is in the range of 3 μm to 15 μm. Preferably, the diameter of the silver wire is in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and the length is in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm. Preferably, in order to obtain a structure in which the silver wire is wound by the carbon nanotube, the ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.3-1000.
[0062] Preferably, in order to better achieve the mechanical and electrical effects of the lithium-carbon composite material described in detail above, based on the weight of the lithium-carbon composite material as 100%, the weight of the carbon nanotubes accounts for 2-75% by weight, preferably 7-55% by weight, and more preferably 11-46% by weight; based on the weight of the lithium-carbon composite material as 100%, the weight of the silver wire accounts for 0.5-25% by weight, preferably 1.2-18% by weight, and more preferably 3.5-14.5% by weight; based on the weight of the lithium-carbon composite material as 100%, the weight of the lithium alloy accounts for 2-57% by weight, preferably 3.6-48% by weight, and more preferably 5.4-34.5% by weight; and based on the weight of the lithium-carbon composite material as 100%, the weight of the metallic lithium accounts for 2-95.5% by weight, preferably 10-87% by weight, and more preferably 21-75% by weight.
[0063] According to the technical solution of the present invention, the lithium alloy is a compound lithium alloy. Preferably, the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
[0064] According to another aspect of the present invention, there is provided a method for preparing a lithium-carbon composite material, the method comprising the following steps:
[0065] (a) dispersing carbon nanotubes, silver wires, a binder and a cross-linking agent in a solvent to prepare a dispersion;
[0066] (b) treating the dispersion at high temperature to prepare a carbon sintered porous framework containing the carbon nanotubes and the silver wires;
[0067] (c) adding a lithium alloy to molten metallic lithium to prepare a lithium melt containing the lithium alloy;
[0068] (d) immersing the carbon sintered porous skeleton containing the carbon nanotubes and the silver wires into the lithium melt containing the lithium alloy, so that the lithium melt containing the lithium alloy enters the voids of the carbon sintered porous skeleton; and
[0069] (e) taking out the impregnated carbon sintered porous skeleton from the lithium melt, casting an ingot and cooling it to obtain the lithium-carbon composite material.
[0070] Preferably, in order to better achieve the mechanical and electrical effects of the lithium-carbon composite material described in detail above, the carbon nanotubes are multi-walled carbon nanotubes.
[0071] Preferably, the diameter of the carbon nanotube is in the range of 1 nm to 100 nm, preferably 5 nm to 65 nm, more preferably 7 nm to 48 nm, and the length is in the range of 3 μm to 15 μm. Preferably, the diameter of the silver wire is in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and the length is in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm. Preferably, in order to obtain a structure in which the silver wire is wound by the carbon nanotube, the ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000.
[0072] There is no particular restriction on the specific type of the binder that can be used in the present invention. Preferably, the binder is selected from one or more of polyvinyl alcohol, polyvinylidene fluoride, polybutylene styrene, polystyrene, polycarboxyl cellulose, cyanoacrylate, polyacrylic acid, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organic fluorine polymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethyl hydroxybenzoate and its derivatives, monosaccharide or polysaccharide polymers.
[0073] There is no particular limitation on the specific type of cross-linking agent that can be used in the present invention. Preferably, the cross-linking agent is selected from one or more of carbomer, benzoyl peroxide, diethylenetriamine, hydrated sodium borate, cellulose derivatives and isothiazolinone.
[0074] There is no particular restriction on the specific type of the solvent that can be used in the present invention. Preferably, the solvent is selected from one or more of water, tetrachloroethylene, toluene, turpentine, acetone, methyl acetate, ethyl acetate, pentane, n-hexane, cyclohexane, octane, lemon essence, alcohol, xylene, toluene cyclohexanone, isopropyl alcohol, ether, propylene oxide, methyl butyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, acetonitrile, pyridine, phenol and ethylenediamine.
[0075] Preferably, the high temperature treatment comprises heating the dispersion at a temperature of 350° C. to 800° C. for 1 to 5 hours.
[0076] Preferably, the temperature of the molten metallic lithium is in the range of 200°C to 2500°C.
[0077] Preferably, the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
[0078] Preferably, in step (a), the weight ratio of the binder, the cross-linking agent and the carbon nanotubes is (5-65): (2-25): (10-93).
[0079] Preferably, in the carbon sintered porous skeleton, the silver wires are entangled by the carbon nanotubes and are interspersed in the carbon sintered porous skeleton.
[0080] Preferably, the pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g. In addition, preferably, the porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%.
[0081] Preferably, the lithium-carbon composite material has a sheet structure, and a thickness of the lithium-carbon composite material is in a range of 1 μm to 5 μm.
[0082] Another aspect of the present invention provides a negative electrode, which comprises the lithium-carbon composite material described above, or comprises the lithium-carbon composite material prepared by the preparation method described above.
[0083] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0084] Example
[0085] In the present invention, unless otherwise specified, the reagents used are commercial products and are used directly without further purification. In addition, the "%" mentioned is "% by weight", and the "parts" mentioned are "parts by weight".
[0086] Test Method
[0087] According to the test methods described in detail below, the structural strength and electrical performance (battery cycle) tests were performed on the lithium-carbon composite negative electrodes prepared in the following embodiments and comparative examples.
[0088] Structural strength test
[0089] The test specimens were cut from the lithium-carbon composite sheets prepared in the following examples and comparative examples. The specimen size was: 87.5 mm long × 12.5 mm wide. Three specimens were cut from each material and subjected to a tensile test on a tensile test equipment (model BT series, manufacturer Shenzhen Beite Instrument Equipment Co., Ltd.). Specifically, the test steps refer to "GB-228-87 Metal Tensile Test Method". The results are shown in Table 1 below.
[0090] Battery cycle test
[0091] The lithium-carbon composite sheet prepared in the following examples and comparative examples was used as the negative electrode to assemble a button-type half-cell with a metal lithium counter electrode. The diaphragm was a PP / PE composite diaphragm, and the electrolyte was a 1M LiPF6 organic solution, wherein the organic solvent contained ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 1:2 (volume ratio). The assembled button cell was subjected to a charge-discharge test, with a charge-discharge current of 2 mA and a charge-discharge time of 1 hour. The cycle was continued until the battery life expired, and the charge-discharge times were recorded. The test results are displayed on Figure 3 .
[0092] Example 1
[0093] Carbon nanotubes (GTC-304 purchased from Shandong Dazhan Nanomaterial Co., Ltd., with a diameter of 15-25 nm and a length of 5-15 μm), silver wires (silver wires purchased from Suzhou Nofei Nanotechnology Co., Ltd., with a diameter of 80 nm and a length of 73.5 μm), a binder polyvinyl alcohol and a cross-linking agent benzoyl peroxide were dispersed in deionized water to prepare a dispersion, wherein the weight ratio of the carbon nanotubes, the silver wires, the binder and the cross-linking agent was 9:4.5:0.5:1.
[0094] The dispersion is placed in an inert atmosphere protection furnace for high temperature treatment (treatment temperature is 500° C., treatment time is 2 hours) to prepare a carbon sintered porous framework containing the carbon nanotubes and the silver wires. Figure 1 The scanning tunneling microscope (SEM) image of the carbon sintered porous framework containing carbon nanotubes and silver wires prepared in Example 1 of the present invention is shown. Figure 1 It can be seen that the silver wire with a diameter of 80nm runs through the carbon sintered porous skeleton, the surface of the silver wire is rough, and carbon nanotubes are entangled.
[0095] Furthermore, a lithium aluminum alloy (lithium and aluminum element mass ratio of 4:1) was added to the molten metal lithium at a temperature of 800° C. while stirring to prepare a lithium melt containing the lithium alloy.
[0096] The carbon sintered porous skeleton containing the carbon nanotubes and the silver wires is immersed in the lithium melt containing the lithium alloy so that the lithium melt containing the lithium alloy enters the voids of the carbon sintered porous skeleton. Subsequently, the impregnated carbon sintered porous skeleton is taken out from the lithium melt, cast into an ingot, and cooled to obtain a lithium-carbon composite material. Figure 2 The scanning tunneling microscope (SEM) photo of the lithium-carbon composite material prepared in Example 1 of the present invention is shown. Figure 2 It can be seen that a small amount of carbon nanotube skeleton is exposed on the surface of the lithium-carbon composite material, and part of the voids in the carbon nanotube skeleton are filled with metallic lithium and lithium aluminum alloy. EDX energy spectrum analysis of the specific structure of the lithium-carbon composite material proves that lithium alloy and metallic lithium exist simultaneously in the voids of the carbon sintered porous skeleton.
[0097] The lithium-carbon composite material is used to prepare a lithium-carbon composite sheet with a thickness of 50 microns through extrusion and rolling.
[0098] The obtained lithium-carbon composite sheet was tested according to the structural strength test method and battery cycle test method described in detail above.
[0099] Example 2
[0100] A lithium-carbon composite sheet was prepared in a similar manner to Example 1, except that the lithium-aluminum alloy was replaced with a lithium-indium alloy (the element mass ratio of lithium to indium was 4:1). The obtained lithium-carbon composite sheet was tested according to the structural strength test method and battery cycle test method described in detail above.
[0101] Example 3
[0102] A lithium-carbon composite sheet was prepared in a similar manner to Example 1, except that the lithium-aluminum alloy was replaced with a lithium-boron alloy (the element mass ratio of lithium to boron was 4:1). The obtained lithium-carbon composite sheet was tested according to the structural strength test method and battery cycle test method described in detail above.
[0103] Example 4
[0104] A lithium carbon composite sheet was prepared in a similar manner to Example 1, except that the silver wire (a silver wire purchased from Suzhou Nofi Nanotechnology Co., Ltd., with a diameter of 80 nm and a length of 73.5 μm) was replaced with a silver wire (a silver wire purchased from MacLean Reagent Network, with a diameter of 3 μm and a length of 23 μm). The obtained lithium carbon composite sheet was tested according to the structural strength test method and battery cycle test method described in detail above.
[0105] Comparative Example 1
[0106] A lithium-carbon composite sheet was prepared in a similar manner to Example 1, except that no silver wire was used in the preparation. The obtained lithium-carbon composite sheet was tested according to the structural strength test method and battery cycle test method described in detail above.
[0107] Comparative Example 2
[0108] A lithium-carbon composite sheet was prepared in a similar manner to Example 1, except that no lithium-aluminum alloy was used in the preparation, and only molten metallic lithium was used to impregnate the carbon sintered porous framework. The obtained lithium-carbon composite sheet was tested according to the structural strength test method and battery cycle test method described in detail above.
[0109] Comparative Example 3
[0110] Commercially available pure lithium ribbons with a thickness of 50 μm were used to carry out the structural strength tests and battery cycle tests described in detail above.
[0111] Table 1 Tensile test results of materials of Examples 1-4 and Comparative Examples 1-3
[0112]
[0113] It can be seen from the above table that the pure metal lithium belt used in Comparative Example 3 has a larger elongation distance under a smaller tensile force, and the pure metal lithium belt has weak tensile strength. After adding nano silver wire to the pure metal lithium belt or replacing the pure metal lithium belt with lithium alloy, that is, Comparative Example 2 and Comparative Example 1, a larger tensile force is required to break the material. The present invention uses a combination of lithium alloy and silver wire, that is, Examples 1-4, which have a greater tensile strength. During the tensile test, the material can only be broken under a larger tensile force.
[0114] Figure 3 The cycle curves of the batteries prepared in Examples 1-4 and Comparative Examples 1-3 measured according to the battery cycle test method described in detail above are shown. Figure 3It can be seen that the cycle life of button cells containing lithium alloys (Examples 1-4 and Comparative Example 1) is longer than that of button cells containing pure metallic lithium (Comparative Examples 2-3). In addition, the cycle life of the button cell of Example 1 containing lithium aluminum alloy is significantly longer than that of the button cells of Example 2 containing lithium indium alloy and Example 3 containing lithium boron alloy. Without being bound by theory, it is speculated that this is mainly because the mass of indium atoms in lithium indium alloy is larger, and the dispersion uniformity in the whole material is not as good as that of aluminum atoms in lithium aluminum alloy. In addition, boron atoms in lithium boron alloy are non-metallic atoms. Although they can form a skeleton structure to inhibit lithium dendrites, the skeleton conductivity is slightly poor. The above reasons lead to the battery cycle life in Examples 2 and 3 being lower than that in Example 1. The reason why the battery cycle life of Example 4 using silver wire with a diameter of 3 microns is significantly reduced compared with that of Example 1 using silver wire with a diameter of 80nm may be related to the uniformity of the dispersion of silver wire in the material matrix.
[0115] Obviously, those skilled in the art can make various changes and modifications to the present disclosure without departing from the spirit and scope of the present disclosure. Thus, if these modifications and variations of the present disclosure fall within the scope of the claims of the present invention and their equivalents, the present disclosure is also intended to include these modifications and variations.
Claims
1. A lithium-carbon composite material, comprising a carbon sintered porous skeleton containing carbon nanotubes and silver wires, wherein the voids of the carbon sintered porous skeleton are filled with lithium alloy and metallic lithium.
2. The lithium-carbon composite material according to claim 1, wherein the lithium-carbon composite material satisfies one or more of the following: The silver wire is entangled by the carbon nanotubes and interspersed in the carbon sintered porous framework; The pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g; The porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%; The lithium-carbon composite material has a sheet structure, and the thickness of the lithium-carbon composite material is in the range of 1 μm to 5 μm; The carbon nanotubes are multi-walled carbon nanotubes; The carbon nanotubes have a diameter in the range of 1 nm to 100 nm, preferably 5 nm to 65 nm, more preferably 7 nm to 48 nm, and a length in the range of 3 μm to 15 μm; The silver wire has a diameter in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and a length in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm; and The ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000.
3. The lithium-carbon composite material according to claim 1, wherein the lithium-carbon composite material satisfies one or more of the following: Based on the weight of the lithium-carbon composite material being 100%, the weight of the carbon nanotubes accounts for 2-75 weight %, preferably 7-55 weight %, and more preferably 11-46 weight %; Based on the weight of the lithium-carbon composite material being 100%, the weight of the silver wire accounts for 0.5-25 weight %, preferably 1.2-18 weight %, and more preferably 3.5-14.5 weight %; Based on the weight of the lithium-carbon composite material being 100%, the weight of the lithium alloy accounts for 2-57 weight %, preferably 3.6-48 weight %, and more preferably 5.4-34.5 weight %; and Based on the weight of the lithium-carbon composite material being 100%, the weight of the metallic lithium accounts for 2-95.5% by weight, preferably 10-87% by weight, and more preferably 21-75% by weight.
4. The lithium-carbon composite material according to claim 1, wherein the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
5. A method for preparing a lithium-carbon composite material, the method comprising the following steps: (a) dispersing carbon nanotubes, silver wires, a binder and a cross-linking agent in a solvent to prepare a dispersion; (b) treating the dispersion at high temperature to prepare a carbon sintered porous framework containing the carbon nanotubes and the silver wires; (c) adding a lithium alloy to molten metallic lithium to prepare a lithium melt containing the lithium alloy; (d) immersing the carbon sintered porous skeleton containing the carbon nanotubes and the silver wires into the lithium melt containing the lithium alloy, so that the lithium melt containing the lithium alloy enters the voids of the carbon sintered porous skeleton; and (e) taking out the impregnated carbon sintered porous skeleton from the lithium melt, casting an ingot and cooling it to obtain the lithium-carbon composite material.
6. The method for preparing a lithium-carbon composite material according to claim 5, wherein the method for preparing the lithium-carbon composite material satisfies one or more of the following items: The carbon nanotubes are multi-walled carbon nanotubes; The carbon nanotubes have a diameter in the range of 1 nm to 100 nm, preferably 5 nm to 65 nm, more preferably 7 nm to 48 nm, and a length in the range of 3 μm to 15 μm; The silver wire has a diameter in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and a length in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm; The ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000; The binder is selected from one or more of polyvinyl alcohol, polyvinylidene fluoride, polybutylene styrene, polystyrene, polycarboxycellulose, cyanoacrylate, polyacrylic acid, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organic fluorine polymer, organic siloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethyl hydroxybenzoate and its derivatives, monosaccharide or polysaccharide polymers; The cross-linking agent is selected from one or more of carbomer, benzoyl peroxide, diethylenetriamine, hydrated sodium borate, cellulose derivatives and isothiazolinone; and The solvent is selected from one or more of water, tetrachloroethylene, toluene, turpentine, acetone, methyl acetate, ethyl acetate, pentane, n-hexane, cyclohexane, octane, lemon essence, alcohol, xylene, toluene cyclohexanone, isopropanol, ethyl ether, propylene oxide, methyl butyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, acetonitrile, pyridine, phenol and ethylenediamine.
7. The method for preparing a lithium-carbon composite material according to claim 5, wherein the method for preparing the lithium-carbon composite material satisfies one or more of the following items: The high temperature treatment comprises heating the dispersion at a temperature of 350° C. to 800° C. for 1 to 5 hours; The temperature of the molten lithium metal is in the range of 200°C to 2500°C; The lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy; and In step (a), the weight ratio of the binder, the cross-linking agent and the carbon nanotubes is (5-65):(2-25):(10-93).
8. The method for preparing a lithium-carbon composite material according to claim 5, wherein the method for preparing the lithium-carbon composite material satisfies one or more of the following items: In the carbon sintered porous framework, the silver wire is entangled by the carbon nanotubes and is interspersed in the carbon sintered porous framework; The pore volume of the lithium carbon composite material is in the range of 0.5 ml / g to 3.5 ml / g, preferably 0.9 ml / g to 2.5 ml / g; and The porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%. 9 . The method for preparing a lithium-carbon composite material according to claim 5 , wherein the lithium-carbon composite material has a sheet structure, and a thickness of the lithium-carbon composite material is in a range of 1 μm to 5 μm. 10 . A negative electrode, comprising the lithium-carbon composite material according to claim 1 , or comprising the lithium-carbon composite material prepared by the preparation method according to claim 5 .